The Influence of Fanaticism and Product Quality on Official Merchandise Purchase Decisions at Graha Persib Bandung (Case Study of Persib Fans in Bandung City) - Muhammad Adli HADYAN; Desfitriady DESFITRIADY; Syipa Nur LUTHPIAH (Journal of Entrepreneurial and Business Diversity, 2025)
Purpose:This study aims to examine the influence of fanaticism and product quality on the purchasing decisions of official Persib Bandung merchandise among fans in Bandung City.Methodology:This study uses a quantitative approach with a survey method, distributing questionnaires to 96 respondents who are consumers of official Persib merchandise to collect data.Findings:The research results show that both fanaticism and product quality have a positive and significant impact on purchasing decisions. Fanaticism is generally considered strong, although aspects of long-term loyalty and social engagement still have some weaknesses. Similarly, product quality is considered quite good, but there are areas for improvement, particularly regarding the design and durability of merchandise to better align with consumer expectations.Implication:This study concluded that increased fanaticism and product quality can drive purchasing decisions for official Persib Bandung merchandise. Product recommendations include strengthening the emotional bond between fans and the club through creative marketing strategies and maintaining consistent product quality to compete with pirated merchandise.